Organic waste recycling - Polprasert, Chongrak. (Wiley, 1989)
This book is a guide to the principles and practice of organic waste recycling, it addresses low-cost waste recycling technologies utilising microbial and natural processes. A wide range of topics is covered, opening with a discussion of the need for and the problems involved in organic waste recycling. The characteristics of a number of organic waste materials from a variety of sources, and the pollution and health risks which may be associated with them are described. The central core of the book presents a broad range of technologies used in the recycling of organic waste materials to produce valuable products such as : fertiliser, biogas, algae, fish and irrigated crops. Each recycling technology is described with respect to : objectives, benefits and limitations, environmental requirements, design criteria of the process, use of recycled products and public health aspects. This second edition has been completely revised and up-dated. It includes new sections on: waste minimisation and clean technology, application of constructed wetlands and regulatory aspects of waste disposal and recycling. Case studies of successful waste recycling programs are included and exercises for solving both theoretical and practical problems are given.